NAGA: multi-blockchain based decentralized platform architecture for cryptocurrency payment - Dendej Sawarnkatat; Sucha Smanchat (Institute of Advanced Engineering and Science, 2022)
Paying for electronic commerce products with cryptocurrencies is an increasingly popular method. However, the situations where a seller expects one specific cryptocurrency as a payment while a buyer only possesses another, inevitably create inconvenience to the buyer, which may lead to cancellation of purchase. In this paper, we propose a light-weighted software architecture of a payment system called NAGA platform that works with a number of crypto blockchain networks to support cross-cryptocurrency payments where buyers can pay in one currency, and the seller automatically receives another of his/her choice. This minimizes the complexity and inconvenience of the buyer, leading to an increase in sales and revenues of the electronic commerce system. With the built-in crypto exchange, crosscryptocurrency payment can be processed with real-time exchange rates that enables both buyers and sellers to receive cryptocurrency of their preferred choices.